EU Commission proposal for 2021-2027 budget: Lost opportunities - Kristina van Deuverden (DIW Weekly Report, 2018)
In May, the EU Commission presented its proposal for the EU budget for 2021 to 2027-a period of change for the EU. Not only will Great Britain's exit from the Union leave a significant hole in the budget, but at the same time the budget must cover a vast range of additional requirements. Current international policy developments are already demanding the EU acting as a community, and the European project will continue to require a high level of investment. For managing this balancing act expenditure cuts in traditional areas are indispensable. But the Commission's lopsided proposal relies on higher revenue. Currently, the Commission is planning fund allocations in the absence of a policy strategy for the years after 2020.
Keywords: H6; H7; H8; 330; public finance; budget; European Union